P16, Ki67, P53, and WT1 Expression in Uterine Smooth Muscle Tumors: An Adjunct in Confirming the Diagnosis of Malignancy in Ambiguous Cases. (4th May 2021) - Delgado, Bertha; Dreiher, Jacob; Braiman, Dana; Meirovitz, Mihai; Shaco-Levy, Ruthy
Abstract : The diagnosis of uterine smooth muscle tumors is sometimes difficult, as these tumors may show worrisome features, suspicious for but not diagnostic of malignancy. The recommended immunohistochemical panel in this setting is currently under debate. In this study, we aimed to find a panel of immunohistochemical stains that would be helpful in determining the correct diagnosis in ambiguous uterine smooth muscle tumors, with an emphasis on investigating the possible usefulness of the WT1 antibody. Uterine leiomyomas were found to be immunoreactive with WT1. Since a previous study reported on the lack of immunoreactivity of uterine leiomyosarcomas with WT1, we speculated that WT1 might be useful in this setting. We retrospectively reviewed the medical charts and slides of 91 patients: 22 with leiomyosarcoma, 15 with smooth muscle tumor of uncertain malignant potential, and 54 with leiomyoma. Immunohistochemical stains for WT1, p16, p53, and Ki67 were performed on each case. We found that immunoreactivity with p16 and Ki67 (>40% and >10% of the tumor cells, respectively) and loss of nuclear expression of WT1 (<10% of the tumor cells) were significantly more common in leiomyosarcomas (all P <0.001). Mutated p53 immunohistochemical staining pattern was significantly more prevalent in leiomyosarcomas than in leiomyomas ( P <0.001). Thus, in diagnostically challenging uterine smooth muscle tumors, we recommend using an immunohistochemical panel composed of Ki67, p16, p53, and WT1. A positive result in either of the former 2 (p16 >40% and/or Ki67 >10%) has the strongest association with leiomyosarcoma (sensitivity: 95.5%, specificity=88.9%, positive predictive value=77.8%, negative predictive value=98.0%).